THE EFFECT OF THE PRICE, PROMOTION, LOCATION, BRAND IMAGE AND QUALITY PRODUCTS TOWARDS THE PURCHASE DECISION OF CONSUMERS AT BENGKEL GAOEL STORE MANADO TOWN SQUARE - Rares, Angelina; Jorie, Rotinsulu Jopie (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
The companies need a management and able to anticipate any competition and can run the company effectively and efficiently. Company should use the resources correctly so they can produce maximum return. Various efforts to create a superior product in marketing activities, a strategy to affect the market by means of seeking business opportunities in the form of products do by companies so this allow them to produce quality products better than before and better than rival products. The purpose of research to know the influence of the price, promotion, location, brand image and the quality of products on the consumer purchase decision either simultaneously and partialy.The type of resources used is associative. Determined based on Â the sample slovin formula, as many as 98. Data analysis used multiple regression methodÂ  to test, the hypothesis on F-test and T-test. The research results show simultaneously price, promotion, location, brands and image quality products significant influence on consumer purchase decision Partiay, evaluation prices and product quality have significant purchase influence of consumer decision while promotion, location and brand image do not have significant n influence on consumer purchase decision. Management of Bengkel Gaoel should more attention to promotion, location and brand image to increase consumer purchase decision. Keywords: price, promotion, location, brand image, product quality, purchase decision